Truth, Silence and Violence in Emerging States : Histories of the Unspoken - Russell, Aidan, 1985- (Milton : Routledge, 2019)
Around the world in the twentieth century, political violence in emerging states gave rise to different kinds of silence within their societies. This book explores the histories of these silences, how they were made, maintained, evaded, and transformed. This book gives a comprehensive view of the ongoing evolutions and multiple faces of silence as a common strand in the struggles of state-building. It begins with chapters that examine the construction of "regimes of silence" as an act of power, and it continues through explorations of the ambiguous limits of speech within communities marked by this violence. It highlights national and transnational attempts to combat state silences, before concluding with a series of considerations of how these regimes of silence continue to be extrapolated in the gaps of records and written history. This volume explores histories of the composed silences of political violence across the emerging states of the late twentieth century, not solely as a present concern of aftermath or retrospection but as a diachronic social and political dimension of violence itself. This book makes a major original contribution to international history, as well as to the study of political terror, human rights violations, social recovery, and historical memory.
6. "A deafening silence" and "A piece of speech": Regimes of silence in an African Counter-Insurgency7. Petitioning Saddam: Voices from the Iraqi archives; 8. The world was silent? Global communities of resistance to the 1965 repression in the Cold War era; 9. A selective silence: Leonid Brezhnev's compromise over the memory of Stalin's crimes; 10. Censorship, indifference, oblivion: The Armenian genocide and its denial; Index.
OCLC-licensed vendor bibliographic record.
Keywords: POLITICAL SCIENCE -- General; POLITICAL SCIENCE -- International Relations -- Diplomacy; POLITICAL SCIENCE -- Political Freedom & Security -- International Security; Political violence -- Developing countries -- History -- 20th century; State-sponsored terrorism -- Developing countries -- History -- 20th century; Collective memory -- Social aspects -- Developing countries